Documentary Analysis Within a Realist Evaluation: Recommendations From a Study of Sexual Assault Referral Centres. (18th September 2021) - Price, Holly; Domoney, Jill; Ariss, Steven; Hughes, Elizabeth; Trevillion, Kylee
Realist approaches are increasingly used in studies of complex health interventions/evaluations to understand how programmes work, for whom and under what circumstances. Mixed-method data sources can be used to generate, refine and test realist programme theories, which explore causal links about the contexts that affect the mechanisms of an intervention and lead to the production of different outcomes. The realist approach provides a framework for a detailed understanding of how a programme functions, aiding with the implementation, refinement or adaptation of interventions. Documentary analysis provides an overview of the theoretical and practical functioning of a service and the ways it is structured to provide interventions. Data are often collected early in the evaluation and can include service specifications, organisational policies and procedures and routine audit data. This paper describes a two-stage process of documentary analysis, where data extraction forms and journey maps are used to explore how Sexual Assault Referral Centres (SARCs) in England respond to the mental health and substance use needs of users. Using documentary analysis as part of a sequential data collection process can be valuable in informing subsequent data sources (e.g qualitative interview schedules can be used to further test and refine theories from a documentary analysis). Considerations for researchers in applying documentary analysis include the value of keeping initial searches broad, to capture documents from a range of sources; the need for clarity about the prioritisation of data sources in the selection process; the benefit in establishing a standardised extraction form that incorporates the wider context within which the intervention functions; taking steps to ensure face validity and transferability during interpretation of data sources; the benefits of transforming information from the data extraction form into a visual journey map.